2020
DOI: 10.31235/osf.io/hf32q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inequality in homeschooling during the Corona crisis in the Netherlands. First results from the LISS Panel.

Abstract: The outbreak of the Corona virus has led to unprecedented measures in education. From March 16, all schools in the Netherlands are closed, and children must keep up with their schoolwork from home. Parents are expected to take a crucial role in this “homeschooling”: they are primarily responsible for ensuring that their children follow the curriculum. In this article I report the first results of a module in the LISS Panel that was designed to map how parents school their children in primary and secondary educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
162
5
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(206 citation statements)
references
References 6 publications
16
162
5
23
Order By: Relevance
“…Moreover, other factors that we did not include in the survey such as educational norms within families might be important in explaining the SES gap. Furthermore, recent research suggests that assessments of parents regarding whether or not they are capable of helping their children with homeschooling during school closures varies by social origin (Bol 2020). Due to dynamics of the public awareness and political responses to the spread of the corona virus, only a subsample of respondents received the COVID-19 module.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other factors that we did not include in the survey such as educational norms within families might be important in explaining the SES gap. Furthermore, recent research suggests that assessments of parents regarding whether or not they are capable of helping their children with homeschooling during school closures varies by social origin (Bol 2020). Due to dynamics of the public awareness and political responses to the spread of the corona virus, only a subsample of respondents received the COVID-19 module.…”
Section: Discussionmentioning
confidence: 99%
“…A rich body of research shows that familial socialisation processes have a direct impact on children's learning success and educational achievement (e.g. Johnson et al 2007;Tsai et al 2017;Bol 2020), and the impact of such processes depends on parental language proficiency, parental norms and values, or motivation. As these factors differ between social strata, learning effort during school closures should differ between students from different social backgrounds.…”
Section: Theoretical Notions and Empirical Backgroundmentioning
confidence: 99%
“…In the UK, parents with graduate level education were found to engage in home-schooling for a greater number of days a week than parents without such education (Anders et al, April 2020). Using nationally representative data from parents in the Netherlands, Bol (2020) finds that students from more advantaged backgrounds 'receive much more parental support and have more resources'. While 75 per cent of parents with higher education feel equipped to support their children, only 40 per cent of parents with lower levels of education express confidence in their ability to offer support.…”
Section: Distance Education During Covid-19mentioning
confidence: 99%
“…More specifically, some teachers indicated that they were considering to take into account the work habits and school development of students during the school shutdown. A prior study showed that Dutch students from advantaged socio-economic backgrounds received more school support during the school shutdown, partly because their parents were better equipped to help (Bol 2020). Relatedly, Dutch students from advantaged socio-economic backgrounds experienced a smaller learning loss during the shutdown (Engzell, Frey, and Verhagen 2020).…”
Section: Discussionmentioning
confidence: 99%